Pinus massoniana somatic embryo maturation, mycorrhization of regenerated plantlets and its resistance to Bursaphelenchus xylophilus - Chen, You-Mei; Fei, Qi; Xia, Xin-Rui; Ke, Xin; Ye, Jian-Ren; Zhu, Li-Hua (Frontiers in Plant Science, 2023)
Pine wilt disease, caused by the pine wood nematode (PWN, Bursaphelenchus xylophilus), is a major quarantine forest disease that poses a threat to various pine species, including Pinus massoniana (masson pine), worldwide. Breeding of PWN-resistant pine trees is an important approach to prevent the disease. To expedite the production of PWN-resistant P. massoniana accessions, we investigated the effects of maturation medium treatments on somatic embryo development, germination, survival, and rooting. Furthermore, we evaluated the mycorrhization and nematode resistance of regenerated plantlets. Abscisic acid was identified as the main factor affecting maturation, germination, and rooting of somatic embryos in P. massoniana, resulting in a maximum of 34.9 ± 9.4 somatic embryos per ml, 87.3 ± 9.1% germination rate, and 55.2 ± 29.3% rooting rate. Polyethylene glycol was identified as the main factor affecting the survival rate of somatic embryo plantlets, with a survival rate of up to 59.6 ± 6.8%, followed by abscisic acid. Ectomycorrhizal fungi inoculation with Pisolithus orientalis enhanced the shoot height of plantlets regenerated from embryogenic cell line (ECL) 20-1-7. Ectomycorrhizal fungi inoculation also improved the survival rate of plantlets during the acclimatization stage, with 85% of mycorrhized plantlets surviving four months after acclimatization in the greenhouse, compared with 37% non-mycorrhized plantlets. Following PWN inoculation, the wilting rate and the number of nematodes recovered from ECL 20-1-7 were lower than those recovered from ECL 20-1-4 and 20-1-16. The wilting ratios of mycorrhizal plantlets from all cell lines were significantly lower than those of non-mycorrhizal regenerated plantlets. This plantlet regeneration system and mycorrhization method could be used in the large-scale production of nematode-resistance plantlets and to study the interaction between nematode, pines, and mycorrhizal fungi.